Effect of varying levels of nitrogen, potassium and calcium nutrition on table grape vine physiology and berry quality - Raath, P. J. ( Pieter Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD(Agric))--Stellenbosch University, 2012.